STRATEGI PEMASARAN HOME INDUSTRY BATIK TULIS HERBAL KOTA MADIUN - Setyo Waloyo, L. Anang; Srimulyani, Veronika Agustini; Purwaningsih, Ch. Endang (Widya Warta, 2017)
Batik, as an original Indonesian culture, is heritage that should be preserved; the manufacturing process of the craft has also been preserved historically since the royal era. Every region in Indonesia even has various styles and motifs. The purpose of this study was to determine the application of marketing mix strategies in the home industries of batik in Madiun City. Based on the results of field observations, interviews, and the analysis of the documentation both by our researchers and the others, the batik artisans in Madiun City already developed a marketing strategy even though it was at the very simple level. Some batik home industries in the city of Madiun used natural dyes for batik color variations; they used colors from the leaves of Ketapang and Mahoni combined with Jambal and Tingi woods. This was done as batik product diversification efforts in the city of Madiun in which chemical dyes (Napthol and Remazol) in the batik home industries were dominant. The other efforts developed were developing a product labeling strategy, promoting the products via internet, and selling the products through exhibitions and fashion shows organized by the batik artisan groups in the city of Madiun. The Batik craftsmen also started developing a branding strategy. We suggest each batik artisan in the city of Madiun develops a distinctive motif so that they can compete each other well. It is similar to any big business competitions in which the businessmen adopt blue ocean strategies.